Inventing a People : Contemporary Art in the Balkans - 1 Bulgaria - Greece - Roumania - Turkey. - Balaci, Ruxandra; Boubnova, Iara; Graur, Teodor; Kortun, Vasif; Paulescu, Cosmin; Rouillé, André; Scaltsa, Matoula (Sofia : National Gallery for Foreign Art, 1999)
Boyadjiev, Luchezar ; Ivanov, Pravdoliub ; Rassim ; Serapionov, Kalin ; Kariotaki, Fotini ; Panayotakis, Stavros ; Sachinis, Xenis ; Xonoglou, Dimitris ; Graur, Teodor ; Paulescu, Cosmin ; Perjovschi, Dan ; SubREAL ; Alptekin, Hüseyin ; Murtezaoglu, Aydan ; Sangar, Bülent ; Altindere, Halil
biografie
Inventing a People : Contemporary Art in the Balkans, National Gallery for Foreign Art, Sofia, January 20 - February 20, 1999 ; Artexpo Foundation, Bucarest, April 15 - May 15, 1999 ; Macedonian Musuem of Contemporary Art, Thessaloniki, June 15 - July 15, 1999 ; Istanbul, September 17 - November 8, 1999
Engels & Frans
boek
Keywords: Balkan; Bulgarije; Griekenland; Roemenië; Turkije